Impacts of Porous Medium on Unsteady Helical Flows of Generalized Oldroyd-B Fluid with Two Infinite Coaxial Circular Cylinders - Ghazi, Ghosoun; Waleed, Alaa (Iraqi Journal of Science, 2021)
This article deals with the influence of porous media on helical flows of generalizedOldroyd-B between two infinite coaxial circular cylinders.The fractional derivative is modeled for this problem and studied by using finite Hankel and Laplace transforms.The velocity fields are found by using the fundamentals of the series form in terms of Mittag-Lefflerequation.The research focused on permeability parameters , fractional parameters(